The Cultural Context of Long Working Hours: Workplace Experiences in Korea. Issue 2 (27th April 2018) - Kim, Sehoon; McLean, Gary N.; Park, Soyoun
Abstract: South Koreans work the longest hours in the world's developed countries. The current body of knowledge is built on western culture and does not sufficiently explain working hours in the South Korean context. Considering the differences between cultures and the cultural influence on employees and organizations, it is useful to understand the experiences of long working hours in South Korea. This phenomenology investigated the perceptions of 16 South Korean employees about their working hours and how individual and organizational contexts, influenced by national culture, are related to long working hours. We found that participants were, to some extent, positive about their long working hours. The factors that influenced working hours included individual affirmative attitudes, group cohesiveness, power dynamics, and ineffective routines and systems. We discovered that the working hours were rooted in both individual and organizational behaviors that are driven by the national culture. Our study contributes to HRD research and practices that incorporate social contexts and provides culturally effective interventions to promote well‐being in the workplace.